Under the Sand Dunes : the Search for the Eliason House and the Socioeconomic Status of its Inhabitants - Robbins, Valerie D. (East Carolina University, 2014)
The Eliason House was built for Fort Macon's commanding officer and family on Bogue Banks, North Carolina. The house stood for 35 years before being burned early in the Civil War and, until 2001, no systematic excavations were conducted at the site. The focus of this research was on archaeological investigations conducted in 2001 and 2011 at the site of the Eliason House. Analysis of this data did not reveal the location of the main house, but did locate remains of ancillary structures at the site. Future investigation into the nature of these structures is recommended.   This study also examined socioeconomic status through the artifact assemblage and the historical record to determine the Eliason House inhabitants were members of the upper middle class. It is important to consider these conclusions preliminary, as the main house has yet to be located and a more complete representation of the artifact assemblage may yet be recovered. As a representation of an Antebellum military household, the status of the Eliason House was compared to the contemporary Hay House. The precursory conclusions presented in this study demonstrate the socioeconomic status for Antebellum military and civilian households, were similar.
Keywords: Archaeology; History; North Carolina; Excavations (Archaeology)--North Carolina--Carteret County; Carteret County (N.C.)--Antiquities; Eliason, William Alexander, -1839; Eliason House (N.C.); Bogue Banks (N.C.); Fort Macon (N.C.)